2010
DOI: 10.2527/jas.2009-1919
|View full text |Cite
|
Sign up to set email alerts
|

Determination of carcass and body fat compositions of grazing crossbred bulls using body measurements1

Abstract: The objectives of this study were to analyze body measurements of 40 crossbred bulls grazing low quality forage with different supplementation strategies, to estimate interrelationships among those measurements and carcass and body compositions, and to develop systems of equations to predict body fat using body and carcass measurements. Eight animals were slaughtered at the beginning of the experiment, and the remaining animals were slaughtered at 90 or 220 d. The biometric measures (BM) were obtained the day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 21 publications
8
40
1
4
Order By: Relevance
“…Similarly, fetal length, chest length, cranial circumference, and hip height were affected in fetuses from ML-fed cows. However, these differences were only about 5% and may not have a significant effect on dairy production, because those characteristics are more related to beef cattle performance (Fernandes et al, 2010;De Paula et al, 2013). Meyer et al (2010a) also observed the same results regarding fetal visceral organ growth for fetuses from beef cows that were fed control and nutrient-restricted diets.…”
Section: Fetal Viscera and Organ Masssupporting
confidence: 78%
“…Similarly, fetal length, chest length, cranial circumference, and hip height were affected in fetuses from ML-fed cows. However, these differences were only about 5% and may not have a significant effect on dairy production, because those characteristics are more related to beef cattle performance (Fernandes et al, 2010;De Paula et al, 2013). Meyer et al (2010a) also observed the same results regarding fetal visceral organ growth for fetuses from beef cows that were fed control and nutrient-restricted diets.…”
Section: Fetal Viscera and Organ Masssupporting
confidence: 78%
“…When using biometric measurements associated to weight to estimate body components, Fernandes et al (2010) also observed high model accuracy and precision.…”
Section: Resultsmentioning
confidence: 87%
“…This concept is supported by the studies of Jones et al (1980) and Belk et al (1991). More recently, other studies (McPhee et al, 2008; Wang et al, 2009; Fernandes et al, 2010) have indicated the generally reported ratio of 1 kg of subcutaneous fat to 1.6 kg of intermuscular fat and a deposit of 720 to 760 g/kg of body fat in the carcass of beef cattle equates to about 50 g/kg of physically separated fat at approximately 230 kg live BW. Using the equation proposed by Guiroy et al (2001) and adding 45 kg to account for extended periods at slow rates of gain (National Research Council, 2000), the adjusted final shrunk BW calculated was 532 kg for the Vietnamese Yellow (Vang) cattle with 220 g/kg of empty body fat.…”
Section: Methodsmentioning
confidence: 79%